Ayurvedic Management of Juvenile Spondyloarthropathy - Sharma, Narinder; Sharma, Suresh; Mahajan, Amit (International Research Journal of Ayurveda & Yoga, 2024)
Spondyloarthropathies, chronic inflammatory diseases of the spine and peripheral joints, and juvenile spondyloarthropathies are inflammatory arthritis before the age of 16 years and are characterized by the involvement of both synovium and enthesis leading to spinal and oligoarticular peripheral arthritis, principally in genetically predisposed (HLA-B27) individuals. In this case study, 14-year-old boy with a chief complaint of inability to stand and walk due to pain and swelling in large joints of the body for the past 1 month with swollen left knee and bilateral hip joints with severe muscle atrophy of thigh, pelvic girdle muscles. He was prescribed at the first visit with Rasnadi Guggulu, 250 mg twice a day (alleviates pain, reduces joint stiffness, and lowers joint inflammation). Lakshadi Guggulu, Simhnad Guggulu 250 mg each and Dashmoolarista 15 ml with equal quantity of water twice daily after meals for a period of 1 week. Shankh vati 250 mg and Kamdudha Ras 250 mg twice daily and Panchkarma, i.e., Vishgarbha tail twice a day followed by baluka Swedana (sand poultice) for local application were added in the treatment for the next (02) 2 weeks. At the 3rd and 4th weeks, there was very good symptomatic relief but general weakness still there, so Ashwagandha preparation (Churna) was started as 1 g twice a day for another 2 weeks. By the end of course of treatment, there was marked decrease in bilateral knee effusion on inspection with no signs of inflammation in any joints of body. The patient was able to walk freely without pain. The use of Ayurvedic (Herbal) formulations and panchakarma procedures are helpful in reducing pain and swelling in patients of spondyloarthropathy. The diseases collectively referred to as spondyloarthropathies include ankylosing spondylitis, psoriatic arthritides, arthritis accompanying inflammatory bowel diseases, and chronic reactive arthritis. Estimates of the prevalence of juvenile ankylosing spondylitis range from 11 to 86/100000 children and psoriatic arthritis from 10 to 15/100000 children. JAS occurs most frequently in older boys, adolescents, and young adults. Human leukocyte antigen – HLA – B27 is strongly associated with JAS (more than 90%) and is found in increased frequency in person having spondyloarthropathies with inflammation of axial skeleton.[1] The principal clinical entities are enthesitis-related arthritis, undifferentiated spondyloarthritis, ankylosing spondylitis, reactive arthritis, psoriatic arthritis, and enteropathic arthritis.[2]